Analysis Of Mathematics Teacher’s Pedagogical Competency and Students’s Numeracy In Solving Numeracy Problems - Epran, Epran; Kusumah, Yaya Sukjaya; Herman, Tatang (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
This study aims to analyze the pedagogical competence of mathematics teachers and students' numeracy level in solving numeracy problems. The research was conducted in one junior high school in Bandung using a qualitative approach and case study design. The subjects of this research were 16 students in grade VIII and one math teacher at a junior high school in Bandung. Data were collected through observation, numeracy tests, and interviews. The numeracy test results showed that four students had a low numeracy level, six were medium, and six were high, with an average numeracy score of 70.625, which was in the medium category based on the indicator scale. Observations and interviews revealed that teachers have good pedagogical competence. Teachers can design learning according to the curriculum, use methods that actively involve students, and provide constructive feedback. However, test results show variations in students' numeracy levels that require adaptive learning strategies significantly to help students with low numeracy. This research emphasizes the importance of problem-based and differentiated learning approaches to improve students' overall numeracy ability. In addition, further evaluation of other factors, such as motivation and learning environment, which may affect students' numeracy ability, is needed.